OPTIMASI PRODUKSI LAPANGAN GEOTHERMAL PADA PERIODE AWAL PENGEMBANGAN DENGAN MENGGUNAKAN METODE NODAL SISTEM ANALISIS - Hasby Nugraha, Irko
Nodal System Analysis is a analysis method to determine the production optimum point of a systemby balancing the reservoir productivity and the operational needs. Principle of this method is making the given system become smaller components. Those components are bordered by some nodes. In this paper, there is a production system model which consist of five production wells, two phase flow pipe, separator, steam pipe, and turbine. This model has a goal to generate electricity 50 MW. First of all, the model has to be breakdown into 4 components that border with 3 nodes where are located at; the first is at start of the two phase pipe, the second is at separator, and the third is at turbine. Afterward, those nodes are analyzed with Nodal System Analysis. The result is the given production system model cannot achieve electricity 50 MW. Furthermore, writer does Nodal System Analysis for various amount of electricity, those are 40 MW, 30 MW, and 20 MW.The optimal production of this field is 30 MW or 6 MW per well. 30 MW as target is predicted would be achieved for 7 years in the initial period of field developmentwith earning 99 million USD revenue. Otherwise, if the initial goal still want to be accomplished so need some additional wells to fulfill 20 MW as lack. Equally important, steam velocity in steam pipe is on the lower range. For this reason,add production wells don’t have to be followed by adding a new steam pipe. It is enough gathering all steam in the existing steam pipe